Creating Sustainability Through Talent Management Improvement: PT USAHA DAGANG INDONESIA - Indrajaya, Amelia Naim; Setiawan, Diego Lana; Marshella, Irene; Tarigan, Joannes; Oktaviana, Nurainy (Sekolah Tinggi Manajemen IPMI, 2024)
This study analyzes the Human Resource (HR) challenges at PT Usaha Dagang Indonesia (ExportHub.id), a private company dedicated to promoting Indonesian products globally through a digital export ecosystem. Despite having a clear vision and mission, PT UDI faces significant HR issues, particularly in planning, recruitment, and people development. The company lacks defined values, a comprehensive HR roadmap, and structured job descriptions, resulting in high employee turnover and unclear career paths. Competency development and performance management systems are underdeveloped, leading to subjective performance evaluations and inadequate career development strategies. Interviews with HR personnel and an examination of internal and external factors revealed these issues. Recommendations include transforming HR functions from administrative to strategic, developing a comprehensive HR roadmap, and implementing objective performance management and career development programs. These strategies aim to enhance HR efficiency, retain talent, and align HR practices with the company's vision, mission, and business goals.